Control interno del inventario de Comercial Don Saúl del cantón Babahoyo, periodo 2021. - Rojas Almeida, María Celeste (2022)
Inventory control is a system that allows management of the stock of a warehouse, both at the entrance and in the permanence or exit. The ultimate goal is to optimize costs and make the best use of stock. Comercial Don Saúl is a microenterprise in the Babahoyo canton in the Province of Los Ríos, dedicated to the sale of groceries and basic necessities, however Comercial Don Saúl presents shortcomings in internal control, due to the fact that the controls of Inventories that are made in the commercial are not carried out properly, it was found that the turnover of inventories carried by the Comercial Don Saúl is too low, which prevents the exact knowledge of the amount of merchandise that is distributed there; as well as the inventory coverage, the same that according to the tabulated data is not the most adequate, preventing its clients from always having the requested products.